Nutritional Cousenling in Patients with Head, Neck and Esophagus Cancer in (Chemo)Radiotherapy - Pootz, Sheila Crstina (2020)
Introduction: The presence of a nutritionist in the radiotherapy sector intends to recover and maintain the nutritional status of the patients. Objective: To compare the results of daily nutritional counseling with weekly nutritional advising for patients with head, neck and esophagus cancer in radiotherapy treatment. Method: 29 patients were assigned to the study and randomly divided into two groups. The intervention group received nutritional advice daily. The standard group received weekly nutritional counseling. For both groups, body weight, calf or calf circumference, global subjective evaluation produced by the patient (ASG-PPP) and calculation of the daily dietary recall were measured. Results: The majority of the participants were male (80%), mean age 62.7 ± 26 years. Oral nutrition therapy was required for 48% of the individuals and at the end of the treatment 60% were in use of enteral nutrition. The mean weight loss in the intervention group was 1.89 ± 2.58 kg compared to the mean weight loss in the standard group of 9.92 ± 6.68 kg (p <0.001). Half of the patients in the intervention group who began treatment categorized by ASG-PPP in A, finished treatment in the same category (41.7%). More than 40% of patients in the intervention group achieved caloric needs during five weeks of treatment. Conclusion: This study found significant results for lower weight loss in patients with daily nutritional counseling. These results may in the future be precursors of guidelines that steer and direct professionals to specific conducts to patients with this profile.